MR sialography using half-Fourier acquisition single-shot turbo spin-echo (HASTE) sequences. - Murakami, R; Baba, Y; Nishimura, R; Baba, T; Matsumoto, N; Yamashita, Y; Ishikawa, T; Takahashi, M (American Journal of Neuroradiology, 1998)
We describe our preliminary experience with the half-Fourier acquisition single-shot turbo spin-echo (HASTE) sequences for MR imaging of the salivary gland ducts. In the majority of patients, the main parotid and/or submandibular gland ducts and large branches within the glands were detectable on MR images obtained in 2 seconds per section and within 3 minutes for the entire examination. MR sialography using HASTE sequences can be combined with conventional MR studies for the salivary glands.